2020
DOI: 10.3389/fcell.2020.586510
|View full text |Cite
|
Sign up to set email alerts
|

Secreted MicroRNA to Predict Embryo Implantation Outcome: From Research to Clinical Diagnostic Application

Abstract: Embryo implantation failure is considered a leading cause of infertility and a significant bottleneck for in vitro fertilization (IVF) treatment. Confirmed factors that lead to implantation failure involve unhealthy embryos, unreceptive endometrium, and asynchronous development and communication between the two. The quality of embryos is further dependent on sperm parameters, oocyte quality, and early embryo development after fertilization. The extensive involvement of such different factors contributes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…The endometrium can also be influenced by the implanting embryo. Several studies identified miRNAs that are expressed by embryos and present in embryo secretions [ 116 , 117 , 118 , 119 , 120 ]. Due to the increasingly common use of IVF techniques, blastocyst spent media have been analysed for miRNA and other biomarkers [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Micrornas and Endometrial Receptivitymentioning
confidence: 99%
See 3 more Smart Citations
“…The endometrium can also be influenced by the implanting embryo. Several studies identified miRNAs that are expressed by embryos and present in embryo secretions [ 116 , 117 , 118 , 119 , 120 ]. Due to the increasingly common use of IVF techniques, blastocyst spent media have been analysed for miRNA and other biomarkers [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Micrornas and Endometrial Receptivitymentioning
confidence: 99%
“…Several studies identified miRNAs that are expressed by embryos and present in embryo secretions [ 116 , 117 , 118 , 119 , 120 ]. Due to the increasingly common use of IVF techniques, blastocyst spent media have been analysed for miRNA and other biomarkers [ 116 , 117 , 118 , 119 , 120 ]. A few previous reviews discussed miRNAs and embryos, often regarding embryo development but also implantation [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Micrornas and Endometrial Receptivitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the sperm RNAs involved in the regulation during the process of fertilization and further embryo development (5), and the extracellular vesicles microRNAs derived from human follicular fluid are involved in critically important pathways (including WNT, MAPK, ErbB, and TGFb signaling pathway) for follicle growth and oocyte maturation, which also explaining the correlation between the lack of extracellular vesicle-delivered RNAs and poorer outcomes among azoospermic men after successful microscopic testicular sperm extraction. Also, these results could represent noninvasive biomarkers of oocyte quality or sperm quality in assisted reproductive technology (75).…”
Section: Extracellular Vesicles and In-vitro Fertilization (Ivf)mentioning
confidence: 99%